2001
DOI: 10.1093/emboj/20.15.4055
|View full text |Cite
|
Sign up to set email alerts
|

The p41 isoform of invariant chain is a chaperone for cathepsin L

Abstract: The p41 splice variant of major histocompatibility complex (MHC) class II-associated invariant chain (Ii) contains a 65 aa segment that binds to the active site of cathepsin L (CatL), a lysosomal cysteine protease involved in MHC class II-restricted antigen presentation. This segment is absent from the predominant form of Ii, p31. Here we document the in vivo significance of the p41-CatL interaction. By biochemical means and electron microscopy, we demonstrate that the levels of active CatL are strongly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 48 publications
7
60
1
Order By: Relevance
“…Thus, the inhibitor p41 acts as a chaperone, maintaining a pool of mature cathepsin L in the endocytic compartment for antigen processing (73). In the absence of this chaperone, mature cathepsin L is degraded with faster kinetics (73). Moreover, the double-chain form of cathepsin L in some antigen-presenting cells is inactive (74), similar to that observed for cathepsin B in the studies reported here.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Thus, the inhibitor p41 acts as a chaperone, maintaining a pool of mature cathepsin L in the endocytic compartment for antigen processing (73). In the absence of this chaperone, mature cathepsin L is degraded with faster kinetics (73). Moreover, the double-chain form of cathepsin L in some antigen-presenting cells is inactive (74), similar to that observed for cathepsin B in the studies reported here.…”
Section: Discussionsupporting
confidence: 76%
“…In antigen-presenting cells, the p41 splice variant of the invariant chain inhibits cathepsin L (72,73). In cells lacking p41, steady-state levels of the double-chain form of cathepsin L are decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations have linked Cat L stability to a chaperone-like activity of the Ii chain alternatively spliced product p41 (30). p41 was detected neither in HeLa-CIITA cells (INF-␥-treated or not), nor in MelJuSo cells (Fig.…”
Section: Which Human Cathepsin Is Responsible For P10 Degradation?mentioning
confidence: 92%
“…However, the net effect of p41 on cathepsin L activity remains unresolved since it also acts as a cathepsin L chaperone and increases active cathepsin L protein levels in bone marrow macrophages [22]. Nonetheless, the ability of p41 to attenuate protease activity may account, at least in part, for its ability to enhance antigen presentation given that proteases can occassionally destroy T cell epitopes as discussed below [23].…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%